2023
DOI: 10.1029/2022wr034127
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Field, Probabilistic, and 2D Numerical Approaches to Assess Gravel Mobility in a Gravel‐Bed River

F. Arnaud,
A. Paquier,
D. Vázquez‐Tarrío
et al.

Abstract: Sediment transport is a key process that affects the morphology and ecological habitat diversity of rivers. As part of a gravel augmentation program to mitigate sediment deficit below a dam, gravel mobility in the Ain River in Eastern France was investigated by tracking of a large amount (n = 1063) of PIT‐tagged gravels in the field, conducting a probabilistic approach based on published tracer studies, and performing two‐dimensional (2D) numerical modeling of flow and bedload transport. This comparative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This would reveal the quantity and size of the sediment that is stored in the reservoirs and the amount that continues to circulate [60,61]. Trackers could also be installed in elements such as gravel to determine their displacement in different future hydrological events [62][63][64][65]. Therefore, the study could be expanded with another series of data if sufficient means were available.…”
Section: Discussionmentioning
confidence: 99%
“…This would reveal the quantity and size of the sediment that is stored in the reservoirs and the amount that continues to circulate [60,61]. Trackers could also be installed in elements such as gravel to determine their displacement in different future hydrological events [62][63][64][65]. Therefore, the study could be expanded with another series of data if sufficient means were available.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lower Ain River, down-ramping rates are relatively low (about 4-6 m 3 s À1 h À1 , i.e. 5.3-9,9 cm h À1 on average, calculated with a 2D-model developed between Pont d'Ain and the confluence with the Rhône River (used in Arnaud et al, 2023 andJudes et al, 2023), Table 1), whereas in the literature, fish stranding is associated with a down-ramping rates higher than 6 cm h À1 for post-emerged trout and higher than 12 and 24 cm h À1 for grayling larvae and juvenile, respectively (Moreira et al, 2019). Schmutz et al (2015) observed a threshold of 15 cm h À1 below which the probability of observing a good fish ecological status is achieved, converging with Halleraker et al (2003) recommendations to reduce down-ramping rates to less than 10-15 cm h À1 .…”
Section: Recommendation For Operational Managementmentioning
confidence: 99%